New species and records of Phanoperla (Plecoptera: Perlidae) from southwestern China - Wang, Yingying; Li, Wenliang; Li, Weihai (Zootaxa, 2022)
A species of Phanoperla, P. wangi sp. nov., is described from Yunnan Province, China as new to science and compared with related species. Phanoperla himalayana Zwick, 1977, P. vietnamensis Zwick, 1986, and P. wieng Sivec & Stark, 2010 are reported as new records from China.